On Equiconvergence of Fourier Series and Fourier Integral - Rakhimov A.A.; Hassan T.B.H.; Rasedee A.F.N.B. (Institute of Physics Publishing, 2024)
In this paper we prove a precise equiconvergence relation between index of the Bochner-Riesz means of the expansions and power of the singularity of the distributions with compact support. Published under licence by IOP Publishing Ltd.